Genome of the parasitoid wasp Cotesia chilonis sheds light on amino acid resource exploitation - Xinhai Ye; Shijiao Xiong; Ziwen Teng; Yi Yang; Jiale Wang; Kaili Yu; Huizi Wu; Yang Mei; Cheng Xue; Zhichao Yan; Chuanlin Yin; Fang Wang; et al. (BMC Biology, 2022)
Abstract Background A fundamental feature of parasitism is the nutritional exploitation of host organisms by their parasites. Parasitoid wasps lay eggs on arthropod hosts, exploiting them for nutrition to support larval development by using diverse effectors aimed at regulating host metabolism. However, the genetic components and molecular mechanisms at the basis of such exploitation, especially the utilization of host amino acid resources, remain largely unknown. To address this question, here, we present a chromosome-level genome assembly of the parasitoid wasp Cotesia chilonis and reconstruct its amino acid biosynthetic pathway. Results Analyses of the amino acid synthetic pathway indicate that C. chilonis lost the ability to synthesize ten amino acids, which was confirmed by feeding experiments with amino acid-depleted media. Of the ten pathways, nine are known to have been lost in the common ancestor of animals. We find that the ability to synthesize arginine was also lost in C. chilonis because of the absence of two key genes in the arginine synthesis pathway. Further analyses of the genomes of 72 arthropods species show that the loss of arginine synthesis is common in arthropods. Metabolomic analyses by UPLC-MS/MS reveal that the temporal concentrations of arginine, serine, tyrosine, and alanine are significantly higher in host (Chilo suppressalis) hemolymph at 3 days after parasitism, whereas the temporal levels of 5-hydroxylysine, glutamic acid, methionine, and lysine are significantly lower. We sequence the transcriptomes of a parasitized host and non-parasitized control. Differential gene expression analyses using these transcriptomes indicate that parasitoid wasps inhibit amino acid utilization and activate protein degradation in the host, likely resulting in the increase of amino acid content in host hemolymph. Conclusions We sequenced the genome of a parasitoid wasp, C. chilonis, and revealed the features of trait loss in amino acid biosynthesis. Our work provides new insights into amino acid exploitation by parasitoid wasps, and this knowledge can specifically be used to design parasitoid artificial diets that potentially benefit mass rearing of parasitoids for pest control.